‘Low- Carbon Future Village’: The story of Qingshan Village, China, and a new journey of international co-learning - Zhang, Wei; Wang, Xinxin; Kumar, Praveen; Chen, Kevin Z. (CGIAR, 2023)
Qingshan Village is located in the northeast of Huanghu Town, Yuhang District, in Hangzhou City, Zhejiang province, China. Coordinated through its Living Labs for People, in collaboration with China Academy of Rural Development of Zhejiang University, School of Economics of Zhejiang University of Finance and Economics, and Government of Yuhang District, the CGIAR Research Initiative on Low-Emission Food Systems (Mitigate+) started developing a research-for-impact partnership with the Qingshan Village in 2023.